Respuesta :

Answer:

D

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]

Simplifying each radical

[tex]\sqrt{27}[/tex]

= [tex]\sqrt{9(3)}[/tex] = [tex]\sqrt{9}[/tex] × [tex]\sqrt{3}[/tex] = 3[tex]\sqrt{3}[/tex]

[tex]\sqrt{12}[/tex]

= [tex]\sqrt{4(3)}[/tex] = [tex]\sqrt{4}[/tex] × [tex]\sqrt{3}[/tex] = 2[tex]\sqrt{3}[/tex]

[tex]\sqrt{48}[/tex]

= [tex]\sqrt{16(3)}[/tex] = [tex]\sqrt{16}[/tex] × [tex]\sqrt{3}[/tex] = 4[tex]\sqrt{3}[/tex]

Then

3[tex]\sqrt{3}[/tex] - 2[tex]\sqrt{3}[/tex] + 4[tex]\sqrt{3}[/tex]

= 5[tex]\sqrt{3}[/tex] → D